Durability of first-line antiretroviral treatment in the Russian Federation: retrospective study - N. V. Sizova; Yu. K. Plotnikova; T. E. Shimonova; O. E. Chernova; E. S. Ivanova; E. S. Obizhaeva; V. F. Achikyan (Журнал инфектологии, 2023)
Objective. To assess durability of antiretroviral therapy in first line in HIV-infected patients in real clinical practice in the Russian Federation and determine association between basic clinical and demographic characteristics and durability of treatment.Materials and methods. A non-interventional retrospective study was conducted collecting data from primary medical records of HIV-infected patients who signed informed consent form and had started antiretroviral therapy in first line. Patients were enrolled if the third component was a non-nucleoside reverse transcriptase inhibitor (NNRTI) or ritonavir boosted protease inhibitor (PI/r) plus two nucleoside reverse transcriptase inhibitors (NRTIs). Also, patients must have been followed up for at least 96 since start of treatment. Durability of therapy was retrospectively assessed at 48±8 and 96±8.Results. 536 patients were enrolled. Percentage of patients without change of therapy was approximately 76% and 60%, and the mean duration of therapy without changes was approximately 47 and 79 weeks at 48±8 and 96±8 weeks,  correspondingly. Durability of treatment was not different for NNRTI+2NRTIs and PI/r+2NRTIs. Only age ≥ 40 years as a basic characteristic was associated with ART change prior to 96 weeks: OR=1.391, 95% CI 1.005-1.925.Conclusions. In real clinical practice in Russia, durability of first-line antiretroviral therapy corresponds published scientific data (in terms of percentage of patients without change of treatment and its duration without change). Durability of treatment and factors associated with its early switch or stop should be investigated in prospective studies further.